Optimalisasi Penerapan Metode Bermain Flashcard untuk Meningkatkan Pemahaman Konsep Bilangan - Putri, Prihastini Oktasari; Sitorus, Siska Mariana; Hidayati, Ika Septi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Introducing children to mathematics is an urgent matter. Most children in the B-Luke class at TK Kristen Kalam Kudus Pematang Siantar struggle to understand number concepts, even though they can count. Therefore, this study aims to use flashcards as a playful medium to help children understand number concepts from 1 to 20. This is a classroom action research with two cycles. The subjects were 11 children from the B-Luke class. Data were collected through observation, post-class tests, and documentation. The data analysis shows that the initial concept understanding ability, which was predominantly at the Developing (MB) level (55%), increased to an average of Very Well Developed (BSB) at 64%. This demonstrates an improvement in understanding number concepts through the use of flashcards and playful methods.